The Effect of Using Digital Storytelling on Students' Listening Comprehension - Puspitasari, Ayuni Iswiyana; Putra, Bambang Arya Wija; Wahjuningsih, Eka (EFL Education Journal, 2024)
This study is a quasi-experimental study using a post-test-only design. The purpose of the study is to determine if there is a significant effect of digital storytelling on the listening comprehension of eleventh-grade students. The population of this research was eight classes of eleventh-grade students at SMAN 1 Kencong in the 2023/2024 academic year. Data was collected through a listening test. The data was statistically analyzed using a t-test with SPSS. Based on the results, the mean score of the experimental group (80.00) was higher than the control group (63.00). The significant (2-tailed) showed a value of 0.000 which was lower than 0.05. The results prove that there is a significant effect of using Digital Storytelling on students' listening comprehension on eleventh-grade students at SMAN 1 Kencong in the 2023/2024 academic year. Therefore, it is suggested to English teachers, students, and future researchers to use the results of this research as a reference.